Cost-Effective Three-Dimensional Graphene/Ag Aerogel Composite for High-Performance Sensing. (1st July 2016) - Lou, Xianghong; Zhu, Chengling; Pan, Hui; Ma, Jun; Zhu, Shenmin; Zhang, Di; Jiang, Xueliang
Abstract: A cost-effective new approach was developed for the fabrication of a three-dimensional reduced graphene oxide/Ag nanoparticle composite, where Ag nanoparticles of 18.0 ± 1.8 nm in diameter were uniformly dispersed throughout a reduced graphene oxide aerogel. When used as a non-enzymatic sensor, the composite demonstrated excellent electrocatalytic performance toward the detection of H2 O2, i.e. a broad linear range of 0.016–27 mmol L −1, high sensitivity of 419.7 μA mmol −1 L cm −2, low detection limit of 6.8 μmol L −1 and superior selectivity against impurities such as citric acid, ascorbic acid and glucose. The superior performance is ascribed to the large interfacial area provided by the three-dimensional aerogel and the enhanced electron transfer by a great number of the fine Ag nanopaticles uniformly dispersed throughout the aerogel.